The molecular basis of p21-activated kinase-associated neurodevelopmental disorders: From genotype to phenotype - Dobrigna, Manon; Poëa-Guyon, Sandrine; Rousseau, Véronique; Vincent, Aline; Toutain, Annick; Barnier, Jean-Vianney (Frontiers in Neuroscience, 2023)
Although the identification of numerous genes involved in neurodevelopmental disorders (NDDs) has reshaped our understanding of their etiology, there are still major obstacles in the way of developing therapeutic solutions for intellectual disability (ID) and other NDDs. These include extensive clinical and genetic heterogeneity, rarity of recurrent pathogenic variants, and comorbidity with other psychiatric traits. Moreover, a large intragenic mutational landscape is at play in some NDDs, leading to a broad range of clinical symptoms. Such diversity of symptoms is due to the different effects DNA variations have on protein functions and their impacts on downstream biological processes. The type of functional alterations, such as loss or gain of function, and interference with signaling pathways, has yet to be correlated with clinical symptoms for most genes. This review aims at discussing our current understanding of how the molecular changes of group I p21-activated kinases (PAK1, 2 and 3), which are essential actors of brain development and function; contribute to a broad clinical spectrum of NDDs. Identifying differences in PAK structure, regulation and spatio-temporal expression may help understanding the specific functions of each group I PAK. Deciphering how each variation type affects these parameters will help uncover the mechanisms underlying mutation pathogenicity. This is a prerequisite for the development of personalized therapeutic approaches.